2011
DOI: 10.1097/igc.0b013e318216cb91
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling and Prognostic Relevance of Circulating Tumor Cells in the Blood of Ovarian Cancer Patients at Primary Diagnosis and After Platinum-Based Chemotherapy

Abstract: This methodological approach might help to identify molecular targets for specific biological therapies. Blood analysis could give additional information complimentary to that obtained by DTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
86
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 39 publications
9
86
1
Order By: Relevance
“…The CellSearch ® system, based on immunomagnetic EPCAM-mediated cell-selection, is the only Food and Drug Administration-cleared system for CTC enumeration and is the most frequently used platform in clinical studies, showing a significant correlation between the presence of CTC and decreased PFS and OS (26 -30 ). Despite the prognostic impact of CTC counts, several molecular methods have been proposed to complement these studies by improving overall detection rates and sensitivity, thus permitting the assessment of molecular markers in CTC of cancer patients (21,(31)(32)(33)(34)(35). By analyzing CTC in our patient cohort, according to Adnatest OvarianCancer, we demonstrated that positivity of at least one of the tumor-associated transcripts EPCAM, MUC1, or MUC16 in the patient's blood was associated with decreased OS, consistent with our previous observation (21 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CellSearch ® system, based on immunomagnetic EPCAM-mediated cell-selection, is the only Food and Drug Administration-cleared system for CTC enumeration and is the most frequently used platform in clinical studies, showing a significant correlation between the presence of CTC and decreased PFS and OS (26 -30 ). Despite the prognostic impact of CTC counts, several molecular methods have been proposed to complement these studies by improving overall detection rates and sensitivity, thus permitting the assessment of molecular markers in CTC of cancer patients (21,(31)(32)(33)(34)(35). By analyzing CTC in our patient cohort, according to Adnatest OvarianCancer, we demonstrated that positivity of at least one of the tumor-associated transcripts EPCAM, MUC1, or MUC16 in the patient's blood was associated with decreased OS, consistent with our previous observation (21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the prognostic impact of CTC counts, several molecular methods have been proposed to complement these studies by improving overall detection rates and sensitivity, thus permitting the assessment of molecular markers in CTC of cancer patients (21,(31)(32)(33)(34)(35). By analyzing CTC in our patient cohort, according to Adnatest OvarianCancer, we demonstrated that positivity of at least one of the tumor-associated transcripts EPCAM, MUC1, or MUC16 in the patient's blood was associated with decreased OS, consistent with our previous observation (21 ). Moreover, this previous report could be complemented by the finding that the presence of CTC likewise constitutes an independent predictor of OS according to multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTCs were detected in 19% of patients before surgery and in 27% after platinum-based chemotherapy. According to their findings, the presence of CTCs significantly correlated with shorter OS before surgery (p = 0.0054) and after chemotherapy (p = 0.047) [32]. In a more recent study, Kuhlmann et al investigated the predictive value of ERCC1-positive CTCs in 143 pre-surgery epithelial ovarian cancer patients.…”
Section: Circulating Tumor Cells (Ctcs)mentioning
confidence: 99%
“…Unlike in breast cancer, the correlation of CTC occurrence before and after chemotherapy was analysed also in ovarian cancer. It was again found, that the presence of CTCs, independent of the time-point of analysis, has no correlation to clinical parameters such as tumour size, grading and tumour histology (176), but is clearly linked to a shorter overall survival (177). Just like in breast cancer studies, also in ovarian cancer a further characterization of CTCs by use of more marker genes, like PPIC, is pursued (178).…”
Section: Recent Developments For Ctc Detection In Ovarian Cancermentioning
confidence: 99%